A Metode Hierarchical Token Bucket Sebagai Pembatas Kecepatan Data Pada Jaringan Samudra Store - Mulyana, Muhammad Rizky; Primajaya, Aji; Solehudin, Arip (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
With the development of online buying and selling transactions which are now increasingly in demand and make it easier for buyers to transact. Samudra store has an internet network to support store needs and make it easier to make buying and selling transactions online and offline. The internet used comes from an ISP modem connected to a computer and channeled through an access point for employee facilities. Because the bandwidth is limited, the internet often feels slow, this causes disruption of transactions during working hours, therefore it is necessary to hold bandwidth management. Hierarchical Token Bucket (HTB) is one method for bandwidth management and simple queue techniques to manage bandwidth, the max-limit given is 1Mbps and the limit-at is 512Kbps. Network Development Life Cycle (NDLC) methodology used in this study, the stages of research are carried out in accordance with the stages in the NDLC. The results of checking the network at the Samudra store show that the Quality of Service at the Samudra store network is included in the